Effect of CO2 Source and N Feast-Famine Cycle Over Chlorella Growth - Kiral, Ummu Gulsum; Akmırza, İlker (Mehmet Sinan Bilgili, 2022)
In this study, changes in biomass concentrations of different Chlorella species in mixed culture medium under Nitrogen (N) feast-famine cycle and different CO2 sources were investigated. Chlorella mixed culture was operated 40 days. To investigate the different CO2 effects, half of the reactors were operated open to the atmosphere, that is, using the CO2 in the atmosphere, and the half of the reactors were closed to the atmosphere and fed with pure CO2. Average biomass growth rates were found to be 10.5 mg/L.day and 9 mg/L.day in reactors operated open to the atmosphere in reactors with and without nitrogen feastfamine cycle, respectively. In the reactors operated with pure CO2 feed, the average biomass growth rates in the reactors with and without nitrogen feast-famine cycle were found to be 4.6 mg/L.day and 2 mg/L.day, respectively. As a result, it has been seen that the business with the N feast-famine cycle has a positive effect on the biomass growth by stressing the microalgae.
6th EurAsia Waste Management Symposium (EWMS) -- OCT 24-26, 2022 -- Istanbul, TURKEY
Keywords: Microalgae; Nitrogen (N) stress; Chlorella Species; Biomass; Feast-Famine Cycle